Rugby Injury Imaging - Watura, Christopher; Hughes, Richard J.; Lee, Justin C. (Seminars in Musculoskeletal Radiology, 2025)
In 1823, when William Webb Ellis picked up the football and ran with it when playing in a school match for Rugby School in England, the game of rugby was born. In 1845, that same school wrote the first rules of the game, and in 1871 the English Rugby Football Union was created. Since that time, the game has flourished and spread across the world, from England to the four corners of the globe. The game of rugby thrives on athleticism, skill, and bravery. Due to the nature of the game, collision-based injuries are common. However, as the sport has grown in the professional modern era, the players are also susceptible to many noncontact injury patterns. The array of injuries encountered in rugby places radiology central to player welfare and injury management. This article illustrates the range of injuries commonly encountered in one of the fastest growing full-contact sports in the world.
Keywords: injury; imaging; magnetic resonance imaging; rugby; computed tomography